Sustainable energy planning with storage, photo voltaics, biomass co-firing forecasting and heat planning - Østergaard, Poul Alberg; Cabrera, Pedro; Johannsen, Rasmus Magni (International Journal of Sustainable Energy Planning and Management, 2025)
This 47th volume of the International Journal of Sustainable Energy Planning and Management presents the most recent work on energy planning with a focus on storage in energy systems, cofiring of biomass in coal-fired power stations forecasting of electricity demand for better planning practise. Analyses demonstrate the potential resources for photo voltaics (PV) in Iraq, and barriers for its implementation in Indonesia, where perceived costs is a dominant barrier. Heat planning is a long-standing focus area of the journal – in this volume with a focus on stakeholder interests and the organisation of the heat planning process. Lastly, this volume presents analyses of links between energy and development in Africa.